Hourly fetal urine production rate in isolated oligohydramnios at term. - Hyun-Joo Seol; Ho Yeon Kim; Geum-Joon Cho; Min-Jeong Oh (PLoS ONE)
Objective The aim of this study was to evaluate the hourly fetal urine production rate (HFUPR) via three-dimensional ultrasonography in women with isolated oligohydramnios and compare with normal pregnant women at term. Materials and methods This was a prospective observational cohort study of 112 women from 34 to 40 6/7 weeks' gestation. They were classified into three groups according to the amniotic fluid index (AFI) and ultrasonographic estimated fetal weight (EFW) as isolated oligohydramnios (defined as AFI below 5% and appropriate EFW corresponding to gestational age) (n = 34) and IUGR (defined as EFW below 5% corresponding to gestational age irrespective amniotic fluid) (n = 17), and normal pregnancy (n = 61). HFUPR was measured using three-dimensional virtual organ computer-aided analysis. Adverse perinatal outcomes in all participants were examined. Results There was no significant difference in HFUPR between patients with isolated oligohydramnios and women with normal pregnancies (median, 40.0 mL/h [interquartile range [IQR] 31.0-66.5] vs. 48.6 [31.5-81.2], p = 0.224). HFUPR was significantly decreased in the IUGR group (13.8 mL/h [IQR 10.1-24.8]), compared to the normal pregnancy group (p<0.001) and the isolated oligohydramnios group (p<0.001). HFUPR was significantly decreased in neonates with adverse perinatal outcomes compared to the control (24.7 mL/h [IQR 13.4-47.4] vs. 43.6 [29.8-79.0], p = 0.016). Conclusion HFUPR was not decreased in patients with isolated oligohydramnios but was decreased in patients with IUGR when compared to normal controls at term.